The long thaw how humans are changing the next 100,000 years of Earth's climate - Archer, David 1960- (Science essentials, 2009)
"In The Long Thaw, David Archer, one of the world's leading climatologists, predicts that if we continue to emit carbon dioxide we may eventually cancel the next ice age and raise the oceans by 50 meters. By comparing the global warming projection for the next century to natural climate changes of the distant past, and then looking into the future far beyond the usual scientific and political horizon of the year 2100, Archer reveals the hard truths of the long-term climate forecast." "Revealing why carbon dioxide may be an even worse gamble in the long run than in the short, this compelling and critically important book brings the best long-term climate science to a general audience for the first time."